2019
DOI: 10.1177/2309499019880915
|View full text |Cite
|
Sign up to set email alerts
|

Is there an optimal timing of administration of single-dose intravenous tranexamic acid in bilateral total knee arthroplasty? A comparison between preoperative and intraoperative dose

Abstract: Purpose: There is no consensus on the optimum timing of administration of tranexamic acid (TA) in bilateral total knee arthroplasty (TKA). We aimed to determine whether the timing of administration of single-dose intravenous TA (either given preoperatively or intraoperatively) has a significant effect on blood loss reduction. Methods: We compared two cohorts of patients with end-stage arthritis of knees who underwent bilateral TKA and were given single-dose intravenous TA (1 g or 15 mg/kg) at different times d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The findings indicated that receiving an IV injection of TXA during surgery resulted in a notably lower reduction in hemoglobin levels on the first day following the operation. However, there was no substantial impact on the need for transfusions or the amount of fluid drainage [ 43 ]. It is assumed that TXA operates under the all-or-nothing rule, which means that the drug is ineffective if its serum concentration falls below a certain threshold.…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated that receiving an IV injection of TXA during surgery resulted in a notably lower reduction in hemoglobin levels on the first day following the operation. However, there was no substantial impact on the need for transfusions or the amount of fluid drainage [ 43 ]. It is assumed that TXA operates under the all-or-nothing rule, which means that the drug is ineffective if its serum concentration falls below a certain threshold.…”
Section: Discussionmentioning
confidence: 99%
“…The ndings indicated that receiving an IV injection of TXA during surgery resulted in a notably lower reduction in hemoglobin levels on the rst day following the operation. However, there was no substantial impact on the need for transfusions or the amount of uid drainage [29]. It is assumed that TXA operates under the all-or-nothing rule, which means that the drug is ineffective if its serum concentration falls below a certain threshold.…”
Section: Discussionmentioning
confidence: 99%
“… 76 A prospective cohort study by Balachandar and Abuzakuk explored the use of preoperative versus intraoperative single dose of IV TXA in patients undergoing bilateral TKA and noted that while patients in the intraoperative group had a significantly lesser decrease in hemoglobin on the first day postoperatively, no significant difference was appreciated with respect to transfusion rates and drain blood loss volume. 77 …”
Section: Dosage and Optimal Timing Of Txa Administrationmentioning
confidence: 99%